2008
DOI: 10.1007/s10815-008-9255-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of men and recipients’ age on the reproductive outcome of an oocyte donation program

Abstract: Present study suggests that age has a detrimental effect on the reproductive outcome of oocyte donation cycles when both men and recipient are > or = 39 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…Also, when the cycles were divided into two groups according to whether a clinical pregnancy was achieved, or according to whether a live birth was achieved, no significant difference was found in male age between the groups, indicating that male aging would not lead to severe influence on fertilization or embryo development in vitro, which was similar to studies of other authors [8][9][10], but disagreed with founding of other authors [11,12].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Also, when the cycles were divided into two groups according to whether a clinical pregnancy was achieved, or according to whether a live birth was achieved, no significant difference was found in male age between the groups, indicating that male aging would not lead to severe influence on fertilization or embryo development in vitro, which was similar to studies of other authors [8][9][10], but disagreed with founding of other authors [11,12].…”
Section: Discussioncontrasting
confidence: 62%
“…Some studies from Europe and USA found that the increase of male age may lead to elevation of miscarriage rate after ART [4,[11][12][13]. We also found that male aging may be related to the increase of pregnancy loss in the first trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 62%
“…For the comparisons of interrater reliability, the kappa coefficient was 0.86 during the abstract review (95% confidence interval [CI] 0.75-0.97) and 0.92 in the full-text stage (95% CI, 0.76-1.0). Finally, of 425 initial references, twelve manuscripts encompassing 12,538 oocyte donation cases were included in the review (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Table 1 summarizes the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the impact of male age on the outcome of assisted reproductive technologies (ART) using the donor egg model are conflicting (20)(21)(22)(23)(24)(25). This model allows controlling for the effects of variation of oocyte quality by female age.…”
mentioning
confidence: 99%